ASPEK HUKUM GLOBALISASI - Muladi, Muladi (JURNAL BISNIS STRATEGI, 1998)
" An  Erosion  of national  sovereignty,  consinent  with the realities  of globalization,  sees  inevitable.  The WTO's  disputes-resolution  panels have  wide-ranging authority  to  investigate  and rule on trade  laws and practises".  (Lodge,   1995)